A systematic review of methods to measure family co‐participation in physical activity. (2nd October 2017) - Uijtdewilligen, L.; Brown, H. E.; Müller‐Riemenschneider, F.; Lim, Y. W.; Brage, S.; van Sluijs, E. M.
Summary: The family environment is key in influencing children's health behaviours. Encouraging family co‐participation in physical activity may therefore be an effective approach to increasing children's physical activity levels. Yet, little is known about how to best assess family co‐participation in physical activity. This review summarizes methods to measure family co‐participation in physical activity, which was defined as joint physical activities including at least one healthy child (0–18 years) and one other family member. Methods were identified through a systematic literature search, cross‐referencing pre‐selected reviews and contacting research groups. Thirty‐seven measurement methods were included. Questionnaires were the most common method used, with the majority assessing frequency of co‐participation and few also assessing duration and type. Reliability and internal consistency of scales were often reported, but rarely specified for the item(s) relevant to co‐participation. Other methods of measuring co‐participation included diaries, event history calendars, direct observations and accelerometry combined with diary, ecological momentary assessment or global positioning systems (GPS). Whilst a large number of measurement methods of family co‐participation in physical activity exist, few are comprehensive and/or report acceptable psychometric properties. Future work should focus on reaching consensus in defining family co‐participation in physical activity, and subsequently developing reliable and valid measures.